EFEKTIVITAS PLATFORM REPETISI JARAK GAMIFIKASI, QUIZLET, DALAM MENINGKATKAN PEMBELAJARAN KOSAKATA PADA SISWA EFL KELAS 5 - Chotimah, Chusnul (Akademika, 2025)
Vocabulary is essential for helping young learners improve their English skills, but many students find it difficult to memorize new words when instruction relies only on traditional memorization techniques. The effectiveness of the gamified spaced repetition platform, Quizlet, in enhancing vocabulary acquisition among grade fifth English as a Foreign Language students is examined in this study. The objective of this research is to improve the students’ vocabulary acquisition using Quizlet in grade 5. An experimental design was used, involving two groups: one experimental group that learned vocabulary with Quizlet and a control group that used conventional teaching methods. Both groups completed a pre-test and a post-test to assess their vocabulary development. Results showed that the experimental group achieved significantly greater improvements in vocabulary than the control group. The use of Quizlet's flashcards, interactive activities, and spaced reviews helped increase engagement, consistent practice, and better retention of words. These findings suggest that Quizlet is a valuable tool for supporting vocabulary growth in young English language learners. The study recommends integrating gamified digital tools into elementary English classes to enhance student motivation and facilitate ongoing vocabulary development.